Evaluasi Ujian Akhir Semester Pendidikan Agama Islam Di SMPN 13 Surakarta - Salma Rafidah; Munib Amaliah Khasanah; Salsabilla Septiana Putri (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research aims to evaluate the final semester exam in the Islamic Religious Education subject at SMPN 13 Surakarta. Evaluation is carried out to assess the extent to which the final semester exam achieves learning objectives and provides an overview of the effectiveness of the evaluation methods used at SMPN 13 Surakarta. This research method involves qualitative analysis and in-depth interviews conducted on December 27 2023 at SMPN 13 Surakarta regarding regarding the teacher's role in preparing for the final semester exam, exam questions, test results, and student responses to the exam.. The final semester exam questions at SMPN 13 Surakarta were prepared by city MGNP, so they were not created internally by the school. The results of the final semester exams are distributed through report cards which will be received by the students' parents. Students' responses to the end-of-semester exams that make them depressed include parents' expectations of the results of the final semester exams. It is hoped that the results of the research will provide useful information for curriculum development and improving the quality of Islamic Religious Education learning at SMPN 13 Surakarta. Apart from that, this research is expected to provide useful information, both for teachers, students and parents. It is also hoped that this research will be research that can be used again as a research reference later.